Investigation of Air Quality and the Effects of Meteorological Factors on Air Pollution in Nevşehir Province - Kahraman Oğuz (Doğal Afetler ve Çevre Dergisi)
Increasing urban air pollution causes important problems affecting the environment and human health. One of the most important sources of urban air pollution is the road transport sector. In addition, local, commercial and industrial activities as well as long range transports contribute significantly to urban air pollution. Just as air pollution affects the environment, there are also factors affecting air pollution. Foremost among these, meteorological factors come first. In this study, it was aimed to evaluate the air quality and number of polluted days exceeding the limit of air pollution in Nevşehir region and to examine the effects of meteorological factors on air pollution in detail. For this purpose, PM10, SO2, air temperature, pressure, wind speed and relative humidity datas of Nevşehir city between 2010-2019 were obtained from the Air Quality Station data of the Ministry of Environment and Urbanization. Trends and slopes of these data were calculated with the methods of Mann-Kendall and Şen tests. Annual, seasonal, monthly and hourly changes of PM10 and SO2 parameters and days exceeding limit were analyzed. In addition, HYSPLIT model outputs were obtained in order to analyze the sources of the 6 highest PM10 values measured. Then, within the scope of the analysis of the effect of meteorological conditions on air pollution in Nevşehir region, the relationship of PM10 and SO2 pollutants with air temperature, pressure, wind speed and relative humidity parameters were examined.